The Influence of Leadership and Work Environment on High School Teachers' Job Satisfaction with Motivation as an Intervening Variable (Case Study in the North Jakarta Education Office I) - Pardamean, Jefferson Agustan; Kasmir, Kasmir (PT FORMOSA CENDEKIA GLOBAL, 2023)
This observation aims to determine the factors that influence the job satisfaction of state secondary school ASN teachers at the North Jakarta I Education Department. The purpose of this research is to answer questions about the job satisfaction of state middle school ASN teachers at the North Jakarta I Education Agency. This observation is focused on teachers of State secondary school ASNs in the North Jakarta Administrative City Regional Education Subcommittee who are members of the teaching team. The sample size was 104 employees and the observation period was set in 2023. This research is quantitative research that uses the Equation Modeling-Partial Least Squares (SEM-PLS) structural model to analyze the data. The research results show that leadership and the work environment have a positive and significant effect on work motivation, job satisfaction, and the relationship between work motivation and job satisfaction.